NEW ABELISAURID MATERIAL FROM THE UPPER CRETACEOUS (CENOMANIAN) OF MOROCCO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Fragmentary cranial bones of dinosaur origin have been recently recovered from the Kem Kem beds (Upper Cretaceous, Cenomanian) of Morocco. They include two incompletely preserved maxillary bones evidencing diagnostic features of abelisaurid theropods. These new finds provide further evidence of Abelisauridae in the Late Cretaceous of Morocco.
Keywords: Theropoda; Abelisauridae; Maxillae; Cenomanian; Northeastern Africa; Morocco